2010
DOI: 10.1111/j.1529-8817.2010.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

NICHE PARTITIONING AND THE COEXISTENCE OF TWO CRYPTIC DICTYOTA (DICTYOTALES, PHAEOPHYCEAE) SPECIES FROM THE CANARY ISLANDS1

Abstract: Coexistence in a homogeneous environment requires species to specialize in distinct niches. Sympatry of cryptic species is of special interest to both ecologists and evolutionary biologists because the mechanisms that facilitate their persistent coexistence are obscure. In this study, we report on two sympatric Dictyota species, D. dichotoma (Huds.) J. V. Lamour. and the newly described species D. cymatophila sp. nov., from the Canary Islands. Gene sequence data (rbcL, psbA, nad1, cox1, cox3, and LSU rDNA) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 60 publications
0
38
0
2
Order By: Relevance
“…For example, in the Canary Islands, the brown alga Dictyota cymatophila Tronholm, M.Sansón & Afonso-Carrillo more frequently occurred in wave-exposed habitats, whereas D. dichotoma (Hudson) J.V.Lamouroux was found in less-exposed areas (Tronholm et al 2010). Additionally, physical conditions related to wave exposure limit the horizontal distribution of marine macroalgae, as found in the intertidal kelp Postelsia palmaeformis Ruprecht from the northeast Pacific (Nielsen et al 2006).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, in the Canary Islands, the brown alga Dictyota cymatophila Tronholm, M.Sansón & Afonso-Carrillo more frequently occurred in wave-exposed habitats, whereas D. dichotoma (Hudson) J.V.Lamouroux was found in less-exposed areas (Tronholm et al 2010). Additionally, physical conditions related to wave exposure limit the horizontal distribution of marine macroalgae, as found in the intertidal kelp Postelsia palmaeformis Ruprecht from the northeast Pacific (Nielsen et al 2006).…”
Section: Discussionmentioning
confidence: 96%
“…In intertidal ecosystems, many studies have previously demonstrated temporal and spatial niche differentiations (e.g. reproductive timing, tidal position and exposure level) among competing taxa, allowing them to coexist at small scales (Benzie et al 2000;De Troch et al 2003;Sampayo et al 2007;Tronholm et al 2010;Lai et al 2011;Zardi et al 2011). For example, within mid-intertidal pools along the northern Gulf of California, the brown alga Sargassum johnstonii Setchell & Gardner grew at a shallower depth than S. sinicola subsp.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, morphological differences between some species are subtle and easily go unnoticed, particularly if specimens are not examined with suffi cient care. For example, using a combination of morphological and molecular data Tronholm et al ( 2010a ) showed that in the Canary Islands Dictyota cymatophila was confused with D. dichotoma for a long time. The two species are frequently found mixed in the fi eld, where they are usually impossible to distinguish; they can be recognized, however, based on differences in the phenology and in microscopic morphological characters.…”
Section: The Order Dictyotalesmentioning
confidence: 98%
“…Several studies have revealed cryptic species within morphologically defined species, falsifying the assumption that speciation events coincide with any morphological differentiation (Tronholm et al 2010a). Therefore, molecular work is currently conducted by us to precisely corroborate the identity of the present population and to evaluate the possibility that it could represent a cryptic species (Marine macroalgae collections in north Patagonian coasts to obtain DNA barcodes: iBol Project, CONICET).…”
Section: Taxonomic Commentarymentioning
confidence: 99%